Moral sensitivity of nursing students: a systematic review - Abdollah Zargar Shadi; Vanaki Zohreh; Mohammadi Eesa; Kazemnejad Anoshirvan (BMC, 2024)
Abstract Background Moral sensitivity is an essential criterion for nurses' professional competence, and it is effective in professional performance and the development of communication between nurse and patient. According to several definitions of moral sensitivity in nursing texts, each of them has examined moral sensitivity from a different aspect, and there are still uncertainties in the field of moral sensitivity of nursing students. Therefore, to clarify the characteristics and dimensions of the concept of moral sensitivity of nursing students, we used the method of concept analysis. Goal To clarify and define moral sensitivity of nursing students. Method For this systematic review, ten databases (PubMed, Scopus, Science Direct, Emerald, Springer, Proquest (open access), ERIC, SID, Irandoc, Magiran) were searched. They were published between 1990 and 2020. Inclusion criteria were having access to the full text of the article, types of studies (quantitative, qualitative, concept analysis, systematic review, and meta-analysis) related to the attributes, antecedents, and consequences of nursing students' moral sensitivity, medical students' moral sensitivity and Ethics education, articles being published in scientific journals in English or Persian language, texts published in non-peer-reviewed journals and letters to the editor were excluded from the data analysis. The methodological quality of the studies was assessed using the Mixed Methods Appraisal Tool 2018 and Prisma ScR Checklist 2020. Rodger's evolutionary concept analysis was used to conduct this study. Results From 361 articles, 38 were included. The results showed moral sensitivity in nursing students improves through specialized ethical knowledge and presence in educational and professional settings. The attributes consist of honest and benevolent communication, compassionate professional practice, intuitive perceiving moral challenges, awareness of the responsibilities and moral consequences of decisions. The moral sensitivity of nursing students improves the quality of nursing care and the effective management of ethical challenges. Conclusion Results can help develop nursing education theories and programs, design appropriate tools to evaluate this concept, and increase the quality of care and management of moral challenges in society and health systems. Limitation This research has only examined Persian and English texts; also, accessing all the international databases was impossible, and more investigation in this field is required.